Analisis Kemampuan Pedagogical Content Knowledge (PCK) Guru IPA Kelas IX SMP Muhammadiyah se-Kota Surakarta Berdasarkan Rencana Pelaksanaan Pembelajaran (RPP) - Sendy, Putra Pradana, Dra. Hariyatmi, M.Si (2017)
Teacher is a person who holds a major role in determining the success of learners to get good learning outcomes. The purpose of this study was to determine the Pedagogical Content Knowledge (PCK) capability of science teachers at ninth grade Muhammadiyah high school in Surakarta in arranging the lesson plan 2016/2017 academic year. The research is a qualitative descriptive. The sampling technique is random sampling study by taking five lesson plan randomly assigned to each teacher. Based on the research that has been done shows that the CK capability of teachers includes not good (22.29%), PK ability is enough (62.29%), and the ability of PCK categorized as good (78.33%). Therefore, the ability of PCK capability of Science teachers at IXth grade Muhammadiyah High School in Surakarta in arranging the lesson plan 2016/2017 Academic Year including good.